Etiopathogenetic Factors of Hepatocellular Carcinoma, Overall Survival, and Their Evolution over Time-Czech Tertiary Center Overview - Hříbek, Petr; Klasová, Johana; Tůma, Tomáš; Kupsa, Tomáš; Urbánek, Petr (Medicina, 2022)
Background and Objectives: Hepatocellular carcinoma (HCC) is the most common form of primary liver cancer with a highly unfavorable prognosis. Aims: Retrospective statistical analysis of patients with HCC in the field of liver cirrhosis treated at our center from the perspective of demography, and the effects of key changes in diagnostic and therapeutic procedures in the last 10 years on overall survival (OS) and earlier diagnosis. Materials and Methods: This study included 170 cirrhotic patients with HCC (136 men, 80%). Demographic and etiological factors and OS were analyzed based on distribution into three groups according to the period and key changes in diagnostic and therapeutic approaches (BCLC classification staging; standardization of protocol for transarterial chemoembolization (TACE) and the introduction of direct-acting antivirals (DAA) for the treatment of chronic viral hepatitis C (HCV); expansion of systemic oncological therapy). Results: The mean age at the time of diagnosis was 69.3 years (SD = 8.1), and etiology was as follows: non-alcoholic steatohepatitis (NASH) 39%, alcoholic liver disease (ALD) 36%, HCV 18%, cryptogenic liver cirrhosis 3%, chronic hepatitis B infection (HBV) 2%, and other etiology 2%. Distribution of stages according to the BCLC: 0 + A 36%, B 31%, C 22%, and D 11%. However, the distribution in the first studied period was as follows: 0 + A 15%, B 34%, C 36%, and D 15%; and in the last period: 0 + A 45%, B 27%, C 17%, and D 11%, and difference was statistically significant (p < 0.05). The median OS for stages 0 + A, B, C, and D was 58, 19, 6, and 2 months, respectively. During the monitored period, there was a visible increase in the etiology of ALD from 30% to 47% and a decrease in HCV from 22% to 11%. In patients treated with TACE (stage B), the median OS grew from 10 to 24 months (p < 0.0001) between the marginal monitored periods. Conclusions: We described a decreasing number of patients with HCV-related HCC during follow-up possibly linked with the introduction of DAA. In our cohort, an improvement in early-stage diagnosis was found, which we mainly concluded as a result of proper ultrasound surveillance, the institution of a HCV treatment center, and increased experience of our sonographers with an examination of cirrhotic patients. Lastly, we described significantly improved overall survival in patients with intermediate HCC treated by TACE, due to the increased experience of interventional radiologists with the method at our facility and an earlier switch to systemic therapy in case of non-response to TACE.
Keywords: Antiviral Agents; Liver Cirrhosis; hepatocelulární karcinom; antivirové látky; výsledek terapie; jaterní cirhóza; lidé; nádory jater; Carcinoma, Hepatocellular; staging nádorů; Treatment Outcome; chronická hepatitida C; chemoembolizace; retrospektivní studie; Liver Neoplasms; Male; Czech Republic; Hepatitis C, Chronic; Česká republika; mužské pohlaví; Retrospective Studies; Neoplasm Staging; Chemoembolization, Therapeutic; Humans